DESCRIPTION OF LINGUISTIC MEANS AND METHODS OF EDUCATION OF TOURISM TERMS IN RUSSIAN, UZBEK AND ENGLISH LANGUAGES (TAMADDUN NURI JURNALI, 2025)
This article discusses the features of the use of tourism terms in the speech of peoples belonging to the Russian, Uzbek and English lenguage systems through contrastive study.